Burnout and Anxiety Among Trauma Nursing Specialties in a Rural Level I Trauma Center. Issue 1 (January 2021) - Cook, Alan; Sigler, Carly; Allen, LaDonna; Peters, Jo Ann; Guthrie, Christiana; Marroquin, Michele; Ndetan, Harrison; Singh, Karan P.; Murry, Jason; Norwood, Scott; Philley, Julie V.
Abstract : Background: Burnout and anxiety compromise physical and mental well-being of nurses and jeopardize patient safety. Personal, professional, and workplace characteristics have been associated with burnout and anxiety across diverse practice settings, yet none in rural, community trauma centers. We sought to identify the severity and predictors of burnout and anxiety in the trauma nursing staff of a rural Level I trauma center. Methods: A convenience sample of trauma nurses from the emergency department (ED), intensive care unit (ICU), and trauma ward was voluntarily surveyed using a demographic questionnaire, the Maslach Burnout Inventory (MBI) subscales: depersonalization (DP), emotional exhaustion (EE), and reduced personal accomplishment, as well as the Generalized Anxiety Disorder seven-item (GAD-7) scale. Multivariable linear regression identified the significant predictors of burnout and anxiety. Results: Ninety-six nurses completed surveys (response rate: 83.5%). Married or divorced status, and ICU or trauma ward job assignments were associated with significantly lower adjusted DP scores. Thus, the model-predicted score for a single ED nurse was 15 versus a predicted score of 7 for a divorced ICU or trauma ward nurse, p < .001 for each group. The GAD-7 model demonstrated that race/ethnicity (Asian compared with White, coefficient: −5.06, p = .03), number of children (2 compared with 0, coefficient: −2.54, p = .02), and job tenure (5–10 years vs. <2, coefficient: −3.18, p = .01) were each associated with fewer GAD-7 points. Conclusion: Depersonalization and anxiety vary across the trauma nursing workforce based on identifiable personal and work-related risk factors. Group-specific, targeted interventions are needed to effectively reduce burnout and anxiety in trauma nursing staff. Abstract : Supplemental Digital Content is Available in the Text.